(untitled) (Research, Society and Development, 2023)
Introduction: The emergency care service is exposed on two fronts, the first of which occurs in the initial approach exposed by the mobile emergency care service (SAMU) that refer patients to the emergency care units (UPA). This whole approach involves a multidisciplinary team. Objective: The objective of this study is to analyze the conduct and the multidisciplinary impact of the implementation of the Emergency Care Units (UPAs) and the Mobile Emergency Care Service (SAMU) in Brazil. Methodology: The work is defined as an integrative literature review. For the elaboration of this article, the databases of scientific articles were used, among them: US National Library of Medicine (PubMed) Latin American and Caribbean Literature in Health Sciences (LILACS) and Virtual Library in Health (VHL) of scientific data up to September 8, 2022, in English, Portuguese and Spanish. As inclusion criteria, the articles used are from the period 2010 to 2022. The keywords “Samu" AND “UPA” AND “professional” were used for the search. Result and discussion: The contact of the Mobile Emergency Care Service (SAMU) , occurs via telephone 192 which, if necessary, will transfer vehicles to the location via the call center and take the patient to the emergency care units (UPA). However, most of the consultations are resolved through the information given via telephone. Conclusion: Since their implementation in Brazil, the UPAs and the SAMU have reduced the mortality of people who are victims of accidents.